الأحاديث الواردة في الكتب المدرسية للتربية الإسلامية في المدارس الحكومية بماليزيا : دراسة تحليلية نقدية - Noor Dashriman bin Noor Kaman (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2013)
The Islamic Education in Public Schools in Malaysia is the title of a series of textbooks used in most public schools in Malaysia. These books consist of a variety of ahadith. Based on the significance of these books, which are widely accepted by Malaysian society and have become sources of reference in teaching, a review and investigation are essential to know the quality of the ahadith mentioned in terms of acceptance and rejection for reasoning. The aim of this research is to study the ahadith which were narrated by other than six hadith collections (kutubus-sittah) which are mentioned in these textbooks by way of takhrij from their original references of hadith and adjudge them through the statements of hadith scholars. Morover, the researcher analyzs the condition of their ruwat or matan to know the status of the ahadith. Through the study of these books, the researcher has found that most of the ahadith are categorized as sahih and hasan, da'if, and even maudu'. In studying the 28 hadith, the researcher found nine of them being sahih, and 11 are hasan, seven are da'if, and one of them is maudu', while none is da'if jiddan.